Запишите выражения в виде одночлена или многочлена стандартного вида:

1)1.4х(0.5х-0.3у)-5(0.4у^2-4ху)+0.2у(8у-5х)=

2)4х-2(х-3)-3(х-3(4-2х)+8)=

3)3х-2((1-3(2х-3-а)-59а-(3х-2а)-4))=

4)(7х^3 у^2-ху)(-2х^2 у^2+5ху^3)=

5)(6а^2+5в^2)(2а^2-4в^2)=

2

Ответы и объяснения

2011-08-14T18:06:04+00:00

1)1,4х(0,5х-0,3у)-5(0,4у²-4ху)+0,2у(8у-5х)=0,7х²-0,42ху-2у²+20ху+1,6у²-ху = 0,7х²+18,58ху-0,4у²

2)4х-2(х-3)-3(х-3(4-2х)+8)=4х-2х+6-3(х-12+6х+8)=4х-2х+6-3(7х-4)=2х+6-21х+12 = 18-19х

3)3х-2((1-3(2х-3-а)-59а-(3х-2а)-4))=3х-2(1-6х+9+3а-59а-3х+2а-4)=3х-2(6-9х-54а)=3х-12+18х+108а = 21х-12+108а

4)(7х³у²-ху)(-2х²у²+5ху³) = -14х⁵у⁴+35х⁴у⁵+2х³у³-5х³у⁴

5)(6а²+5в²)(2а²-4в²)=12а⁴-24а²в²+10а²в²-20в⁴ = 12а⁴-14а²в²-20в⁴

  • ayka89
  • почетный грамотей
2011-08-14T18:14:00+00:00

1)1.4х(0.5х-0.3у)-5(0.4у^2-4ху)+0.2у(8у-5х)=0,7x^2-0,42xy-2y^2+20xy+1,6y^2-xy=0,7x^2-0.4y^2+18.58xy

 

2)4х-2(х-3)-3(х-3(4-2х)+8)=4x-2x+6-3(x-12+6x+8)=2x+6-3x+36-18x-24=18-19x

 

3)3х-2((1-3(2х-3-а)-59а-(3х-2а)-4))=3x-2(1-6x+9+3a-59a-3x+2a-4)=3x-2+12x-18-6a+118a+6x-4a+8=21x+108a-12

 

 

5)(6а^2+5в^2)(2а^2-4в^2)=12a^4-24a^2b^2+10a^2b^2-20b^4=12a^4-14a^2b-20b^4

 

4)(7х^3 у^2-ху)(-2х^2 у^2+5ху^3)=-14x⁵y⁴+35x⁴y⁵+2x³y³-5x²y⁴